Melting heat transfer in boundary layer stagnation-point flow towards a stretching/shrinking sheet in a micropolar fluid - Yacob, N.A.; Ishak, A.R.; Pop, I. (Elsevier, 2011)
The steady boundary layer stagnation-point flow of a micropolar fluid towards a horizontal linearly stretching/shrinking sheet is investigated. A mathematical model is developed to study the heat transfer characteristics occurring during the melting process due to a stretching/shrinking sheet. The transformed non-linear ordinary differential equations governing the flow are solved numerically by the Runge-Kutta-Fehlberg method with shooting technique. It is found that dual solutions exist for the shrinking case, while for the stretching case, the solution is unique. (C) 2011 Elsevier Ltd. All rights reserved.